G502(P) Radiological investigation in suspected child abuse (RISCA). (24th May 2017) - Glenn, K; Powell, C; Harrison, S; Kontos, K
Abstract : Introduction: Children who are suspected to have sustained a non-accidental injury (NAI) are investigated with radiological images and there may be variation in practice Objective/aim: We aimed to identify the standard investigations performed in young children (<2 years old) suspected to have sustained an NAI across all Welsh Health Boards. Methods: A questionnaire was sent out to all 8 Named Doctors for Safeguarding. It focussed on the choice of radiological investigations, the availability of bone scans, the standards for radiological reporting and the safeguarding procedure. Results: Full responses were achieved.; 7/8 centres routinely request a head CT scan in under 1 year olds and 4/8 in under 2 year olds. All centres arrange an initial skeletal survey but only 4 centres arrange a delayed 2nd skeletal survey, 2 centres obtain contemporaneous bone scans but 2 centres do not arrange any follow up imaging. 62.5% of centres stated that their imaging is in accordance with national guidance. All centres practice double reporting. There was appropriate involvement of Children's services throughout. Discussion: There good practice but clear variation across regions which may have significant implications for the child and is not in line with the Welsh Assemblies NHS Prudent health care theme. Less than 2/3 of health boards followed national standards for imaging. This variation will impact safeguarding arrangements and level of disruption to the child and its family. Lack of resources may be the cause of the variation in some cases.